Fractionation and recovery of whey proteins by hydrophobic interaction chromatography - Santos, Maria João (2011)
A method for the recovery and fractionation of whey proteins from a whey protein concentrate (80%, w/w) by hydrophobic interaction chromatography is proposed. Standard proteins and WPC 80 dissolved in phosphate buffer with ammonium sulfate 1M were loaded in a HiPrep Octyl Sepharose FF column coupled to a fast protein liquid chromatography (FPLC) system and eluted by decreasing the ionic strength of the buffer using a salt gradient. The results showed that the most hydrophobic protein from whey is -lactalbumin and the less hydrophobic is lactoferrin. It was possible to recover 45.2% of -lactoglobulin using the HiPrep Octyl Sepharose FF column from the whey protein concentrate mixture with 99.6% purity on total protein basis